A comprehensive review of urinary tract fistulas: the evolution of etiologies, surgical techniques, and contemporary outcomes - Noah Nigro; Gary Shahinyan; Shujian Lin; Rohan G. Bhalla; Brian J. Flynn (Therapeutic Advances in Urology)
Urinary tract fistulas (UTFs) are abnormal connections between the urinary tract and adjacent structures such as the bowel, vagina, or blood vessels. UTFs result in significant personal, social, and financial challenges to patients worldwide. This review investigates the various causes, risk factors, symptoms, and historical evolution of repair techniques of UTFs. This focuses on the shift from open surgery to minimally invasive techniques, particularly the growing utilization of robot-assisted laparoscopic (RAL) approaches. This review emphasizes the growing role of RAL surgery in treating UTFs, citing its advantages of reduced blood loss, low recurrence rates, and decreased postoperative complications while acknowledging challenges such as limited access to the RAL platform and longer surgical times. The study concludes with advocacy for more widespread access to the RAL platform as well as more research, including randomized controlled trials, to further refine the body of evidence and promote patient outcomes.